A phase II study of poziotinib in patients with recurrent and/or metastatic head and neck squamous cell carcinoma. (16th September 2021) - Lee, Ji Hyun; Heo, Seong Gu; Ahn, Beung‐Chul; Hong, Min Hee; Cho, Byoung Chul; Lim, Sun Min; Kim, Hye Ryun
Abstract: Background: In phase I studies, poziotinib has shown meaningful efficacy against various types of cancers. This phase 2 study aimed to investigate the efficacy and safety of poziotinib in recurrent and/or metastatic head and neck squamous cell carcinoma (R/M‐HNSCC). Methods: Overall, 49 patients were enrolled (median age, 62 years; age range, 21–78 years). Patients received a median of two prior treatments including chemotherapy and others and received 12 mg poziotinib orally once daily as part of a 28‐day cycle. The primary endpoint was objective response rate (ORR), and the secondary endpoints were progression‐free survival (PFS) and overall survival (OS). Targeted capture sequencing was performed using available tissues to identify translational biomarkers related to clinical response. Results: ORR was 22.4%, median PFS was 4.0 months (95% confidence interval [CI], 1.8–6.2 months), and median OS was 7.6 months (95% CI, 4.4–10.8 months). The most common treatment‐related adverse events were acneiform rash (85%) and mucositis (77%). A grade 3 or higher adverse event was acneiform rash (3%). Targeted capture sequencing was performed in 30 tissue samples. TP53 and PIK3CA were the most frequently mutated genes (43%), followed by CCND1 (33%) and EGFR (30%). Mutations in ERBB2, ERBB3, and ERBB4, which are HER family genes, were observed in 17%, 13%, and 10% samples, respectively. There was no difference in the frequency of somatic mutations in the HER family genes between the clinically benefitted and non‐benefitted groups. Conclusion: Compared to other pan‐HER inhibitors, poziotinib showed clinically meaningful efficacy in heavily treated R/M‐HNSCC. Clinical trial registration number: NCT02216916. Abstract :